2005
DOI: 10.1139/x05-010
|View full text |Cite
|
Sign up to set email alerts
|

Conifer growth, Armillaria ostoyae root disease, and plant diversity responses to broadleaf competition reduction in mixed forests of southern interior British Columbia

Abstract: Broadleaf trees are routinely removed from conifer plantations during vegetation management treatments, but whether the removal increases tree productivity or affects root disease and plant diversity is unknown. The effects of manual and chemical reduction of paper birch (Betula papyrifera Marsh.) and trembling aspen (Populus tremuloides Michx.) on conifer survival, growth, root disease incidence, and plant community diversity were investigated for 5 years in Douglas-fir (Pseudotsuga menziesii var. glauca (Bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
3
36
2
Order By: Relevance
“…Moreover, they also reported that spruce-birch mixed stands are more productive than the single species stand. Some other investigations in mixed stands also suggested greater productivity than that of pure stands of either species (Simard et al 2005;Newsome et al 2010). According to Kelty (2006) more than two species combinations provide the greatest yield compared to pure stand.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, they also reported that spruce-birch mixed stands are more productive than the single species stand. Some other investigations in mixed stands also suggested greater productivity than that of pure stands of either species (Simard et al 2005;Newsome et al 2010). According to Kelty (2006) more than two species combinations provide the greatest yield compared to pure stand.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, conifer productivity has been shown to increase, following complete removal of broadleaves from the forest (Simard et al 2001). As a result, intensive broadleaf control has been justified to enhance conifer productivity (Lavender et al 1990;Wagner et al 2005) but there are increasing concerns about the associated costs to forest health, timber production and detrimental effects on biodiversity (Simard et al 2005;Kelty 2006). It was shown by different investigations that removal of broadleaves increased the rate of disease and insect infestations among residual conifers (Taylor et al 1994;Simard et al 2001;Hawkins et al 2012a) as well as reduced the habitat quality for cavity nesting birds (Aitken et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional models of forest dynamics predict that regeneration patterns result from competitive interactions with neighbours, but this study showed that facilitation by networks affected interspecific interactions between paper birch and Douglas-fir, encouraging a more diverse tree community. Forests rich in tree species are also more resilient to insect attack and disease than pure Douglas-fir forests where other species have been removed by weeding or thinning (Morrison et al 1988;Woods 1994;Baleshta et al 2004;Simard et al 2005). Complex systems are dynamic, and this is illustrated by dynamic patterns and processes in mycorrhizal networks.…”
Section: Mycorrhizal Network In Complexmentioning
confidence: 99%
“…(Heineman et al 2008), and Armillaria root disease (Armillaria ostoyae Henk.) (Woods 1994;Simard et al 2005), resulting in fewer than 50% of plantations meeting free-growing standards after they have been declared free-growing (Heineman et al 2008).…”
Section: Loss Of Complexitymentioning
confidence: 99%